Effects of Steviol Glycosides on Mitochondrial Energy Metabolism and Oxidative Stress in Liver of Rats with Excessive Exercise Fatigue - Zejin GAO; Heng KANG; Qiao SONG (Shipin gongye ke-ji)
Objective: Using Stevia rebaudiana leaves as experimental materials, stevia glycoside (SG) was extracted and isolated, and its effects on mitochondrial energy metabolism and oxidative stress in the liver of rats with excessive exercise fatigue were investigated. Methods: High-performance liquid chromatography was used to analyze the monomer composition of SG. Rats were randomly divided into a sedentary control group (SC), an exercise-induced fatigue model group (EC), a low-dose SG group (SG-L, 50 mg/kg), a medium-dose group (SG-M, 100 mg/kg), and a high-dose group (SG-H, 200 mg/kg). Rats were orally gavaged with 20 mL/kg and an exercise-induced fatigue model was established through 5 weeks of swimming experiments. Physiological and biochemical metabolic indicators and mitochondrial enzyme activities in rats were measured. Additionally, mRNA expression levels of AMPK, PGC-1α, TFAM, and SIRT1 genes in the hepatic energy metabolism signaling pathway were evaluated. Results: SG accounted for 17.82% of the total glycosides in stevia rebaudiana leaves, with steviol glycoside having the highest proportion (24.26%) and rebaudioside B having the lowest proportion (0.38%). Compared with EC, low, medium, and high doses of SG significantly increased glycogen reserves in rat, the hepatic glycogen and muscle glycogen contents were significantly increased by 12.34%, 56.07%, 91.42% and 33.77%, 76.62%, 131.17% (P<0.05), respectively. Blood lactate and blood urea nitrogen levels were significantly reduced by 16.75%, 31.19%, 44.81% and 19.42%, 28.42%, 40.38% (P<0.05), respectively. Hepatic mitochondrial ATPase, respiratory chain enzyme complexes (CⅠ~Ⅳ), and antioxidant enzyme activities were significantly increased (P<0.05), while malondialdehyde content was significantly decreased (P<0.05), all showing dose-dependency. Furthermore, supplementation with SG activated the hepatic AMPK/PGC-1α energy metabolism regulatory pathway. Compared to EC, SG-L, SG-M, and SG-H significantly increased the mRNA expression levels of AMPK, PGC-1α, TFAM, and SIRT1 (P<0.05). Conclusion: SG can promote hepatic mitochondrial energy metabolism by activating the AMPK/PGC-1α signaling pathway, increasing ATP production, enhancing the anti-fatigue effect in rats, and also reducing hepatic mitochondrial oxidative stress levels, thereby alleviating exercise-induced fatigue in rats.